Adenomatoid odontogenic tumor of the mandible - Kailasam Subramaniam; Manoj Kumar Sachidhanandan; Subha Manoharan; Malarvizhi Elangovan (Wolters Kluwer Medknow Publications, 2012)
Adenomatoid odontogenic tumor (AOT) is a benign odontogenic tumor, which presents as a noninvasive lesion of the jaws with slow but progressive growth. AOT is often misdiagnosed as an odontogenic cyst. It accounts for about 2.2 to 7.1% of all odontogenic tumors. It is predominantly seen in young females, in the anterior maxilla, associated with unerupted canines. This report describes a rare case of AOT in the mandible. This paper highlights the controversies regarding its origin and management in the light of recent findings.